Oracle Database 10g Linux administration - Whalen, Edward (McGraw-Hill, 2005)
Install and configure Oracle Database 10g on a Linux enterprise platform. This book explains how to set up, administer, monitor, and tune Oracle Database 10g on Linux. You will also learn how to implement High Availability solutions as well as handle backup, recovery, and replication. This exclusive Oracle Press guide is the ideal resource for all Oracle DBAs working in a